Multifunctional triboelectric nanogenerator based on flexible and self-healing sandwich structural film. (1st June 2022) - He, Wen; Li, Siyang; Bai, Peijia; Zhang, Ding; Feng, Linlin; Wang, Liteng; Fu, Xiang; Cui, Heng; Ji, Xinyi; Ma, Rujun
Abstract: Triboelectric nanogenerators (TENGs) represent an emerging technology in energy harvesting and sensing applications. The use of self-healing materials can not only improve the service life but also reduce the cost of TENGs. Here, we developed a flexible and self-healing sandwich structural film which is composed of two layers of nitrile butadiene rubber (NBR) with one layer of MXene in the middle. The NBR/MXene/NBR film is capable of self-healing quickly under heating by a hairdryer in 5 s, and even under a skin temperature of ~37 ℃ for 4 h. The as-prepared TENG, which consists of NBR/MXene/NBR film and basketball epidermis, can play the role of a triboelectric sensor (TS). The corresponding sensing capability was demonstrated by tracing finger touch position and monitoring the dribbling posture of a basketball player. Furthermore, the practical application of energy harvester was also explored by combining the NBR/MXene/NBR film with PTFE film. The as-prepared energy harvester can produce a peak-to-peak voltage of 170 V and a current of 160 μA under periodic compressing motion by human hand. This work suggests great potential for developing self-powered TSs and energy harvesters with excellent flexibility, recoverability, and self-healing properties. Graphical Abstract: ga1 Highlights: The NBR/MXene/NBR film is capable of self-healing quickly under heating by a hairdryer in 5 s. The as-prepared TENG, which consists of NBR/MXene/NBR film and basketball epidermis, can play the role of a triboelectric sensor (TS). The high-performance energy harvester was also explored by combining the NBR/MXene/NBR film with PTFE film.